PENDAPAT ANGGOTA-ANGGOTA DPR-RI MENGENAI INDEPENDENSI AUDITOR NEGARA (BPK) - Suharyani Suharyani (Universitas Negeri Yogyakarta, 2005)
PENDAPAT ANGGOTA-ANGGOTA DPR-RI MENGENAI INDEPENDENSI AUDITOR NEGARA (BPK)This research, which is meant as a contribution to state financial control, focusing on the opinion of Indonesian Legislative Assembly members regarding state auditors independence (State Audit Board) viewed from micro perspective. Here are two research questions (a)Do legislative members perceive that state auditors have independence attitude; (b)What factors are influencing the opinion of legislative members regarding state auditors independence. The researcher surveyed 70 legislative members from various faction, commission, education level, gender, and age by personally administered questionnaire technique. Respondents are determined by stratified sampling and convenience sampling method. Data are measured by Likert (ordinal) scale point 5. First hypothesis testing analyze whether legislative members perceive that state auditors are independence performed by mean testing method. While variables which are presumed influencing legislative members opinion are education level, age, gender, and political party (faction) origin (faction). To test whether these four variables by individual influence respondent opinion significantly, the researcher use one way Anova method. The result shows legislative members perceive that state auditors weren’t independence. Except gender variable, the researcher found significant different opinion between respondents group classified by education level, age group, and political party origin. In general, respondents group having degree of S3, elder than 60 year, and coming from Reformasi Faction have a more critical opinion compared to other groups. Keywords : state auditor independence.